Creating a new Scottish musical: Composing and staging The Choir – an interview with Ricky Ross and Dominic Hill. Issue 2 (1st June 2016) - Cooper, Tom
Ricky Ross is a Scottish singer-songwriter. He is lead singer of the band Deacon Blue, which he formed in Glasgow in 1985. He has also released six solo albums, and as a songwriter has written for artists including James Blunt, Jamie Cullum, Nanci Griffith, Ronan Keating, KT Tunstall and Will Young. The Citizens Theatre, known as 'the Citz', is the West of Scotland's principal producing theatre and has produced a wide range of theatre productions over its 70-year history. Its Victorian building in the Gorbals, an area to the south of Glasgow, houses a 500-seat main auditorium and two studio spaces. Dominic Hill became Artistic Director of the Citizens Theatre in 2011, before which he was Artistic Director of the Traverse Theatre in Edinburgh, and joint Artistic Director of Dundee Rep Theatre. He has directed productions extensively around the United Kingdom, including for the Royal Shakespeare Company and Scottish Opera. Ricky Ross' original musical The Choir (book by Paul Higgins, lyrics by Higgins and Ross) was produced by the Citizens Theatre in partnership with Ambassador Theatre Group from 24 October to 14 November 2015. In this interview, Tom Cooper talks to Ricky Ross and Dominic Hill about their compositional and directorial approaches to The Choir, the functioning of the songs within the work, the journey from rehearsal to performance, and the Scottishness of the piece, as well as exploring the Citizens Theatre's new partnership with Ambassador Theatre Group, created to nurture and produce new 'local' musicals.